1999
DOI: 10.1007/bf03190008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diet on the pattern of gastrointestinal biotransformation of netobimin and albendazole sulphoxide in sheep

Abstract: The in vitro biotransformation of the anthelmintic compounds, netobimin (NTB) pro-drug and albendazole sulphoxide (ABZSO), by ruminal fluid obtained from sheep fed either hay or concentrate-based diets was investigated. No metabolic activity was observed in boiled samples of ruminal fluid, which confirms the importance of ruminal microflora in the metabolism of the xenobiotics under investigation. NTB pro-drug was efficiently biotransformed by ruminal fluid in vitro. Albendazole (ABZ) and its sulphoxide deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
(16 reference statements)
2
10
0
Order By: Relevance
“…It has been shown that the gastrointestinal micro¯ora is very active in reductive biotransformation reactions of foreign compounds, particularly those containing sulphoxide groups (Renwick et al 1986). Sheep and cattle ruminal and intestinal contents sulphoreduce the BZDsulphoxide derivatives (ABZSO, oxfendazole) to form the respective thioethers (ABZ and fenbendazole) (Lanusse et al 1992;Virkel et al 1999). Xenobiotic metabolism in parasites seems to be predominantly reductive and hydrolytic (Douch and Buchanan 1979).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the gastrointestinal micro¯ora is very active in reductive biotransformation reactions of foreign compounds, particularly those containing sulphoxide groups (Renwick et al 1986). Sheep and cattle ruminal and intestinal contents sulphoreduce the BZDsulphoxide derivatives (ABZSO, oxfendazole) to form the respective thioethers (ABZ and fenbendazole) (Lanusse et al 1992;Virkel et al 1999). Xenobiotic metabolism in parasites seems to be predominantly reductive and hydrolytic (Douch and Buchanan 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Although the liver is the main site for the biotransformation of xenobiotic compounds, drug metabolism also takes place in extra‐hepatic tissues such as the gastrointestinal tract, which may contribute to reduce the systemic availability of orally administered compounds (Rowland, 1986; Vynckier & Debackere, 1993). The anthelmintics netobimin (an albendazole prodrug) and ABZSO have been shown to suffer extensive biotransformation in ruminal (Virkel et al. , 1999) and intestinal (Lanusse et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 1992) contents collected from sheep and cattle. Those metabolic conversions are mediated by the digestive microflora and both the type of diet (Virkel et al. , 1999) and the antibacterial effect of monensin (Virkel et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the type of feed (lucerne hay diet or concentrate-based diet) was shown in vitro by Virkel et al (1999) who examined the biotransformation of the pro-drug netobimin (NTB) to ABZ and ABZSO by the ruminal fluid obtained from sheep fed hay or concentrates. The biotransformation was found to be more efficient in ruminal fluid obtained from sheep fed a concentrate diet.…”
Section: Albendazole (Abz)mentioning
confidence: 99%